Beyond the ego-history: academic memories as sources of autobiographical research - Silva, Wilton C. L. [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2015)
In Brazil's academic tradition the memorial is a working memories, which is a critical account of the cultural and intellectual history of a university professor, required in process of upgrading of career. This is a privileged manifestation of autobiographical writing in which the personal and intellectual trajectory blend, characterized as one of the rare moments in which it is legitimate of the intellectual to speak about himself. Identified like egohistoire, self-writing or autoethnography the intellectual's autobiographical writing is little studied in the academic Brazilian tradition, although it allows the indentification of normative determinations and configurations of the academic-scientific speech, as well as a multiplicity of identities and references in the narrative process. The academic memorials present the double dimension of institutional and bureaucratic discourse and personal memoirs and narrative, so that it is possible to identify a discursive ethos ranging from the objectified cartesian approach or the subjective hermeneutic perspective, like a rich and polysemous source.
Keywords: Aacademic memories; Self-writing; Autobiography; Intellectual history